Maternal and neonatal infections of herpes simplex virus-1 and cytomegalovirus in Saudi Arabia - Raad M.M. Althaqafi; Mohamed Elrewiny; Ahmed S. Abdel-Moneim (Elsevier, 2020)
It is common practice to screen for human cytomegalovirus (CMV) and herpes simplex virus (HSV) among women with infertility problems, recurrent abortion or exhibiting intrauterine growth restriction during pregnancy. Nonetheless, limited information exists about the incidence of these viruses in Saudi Arabia. The IgG and IgM antibodies of 761 women and 85 of neonates who showed intrauterine growth retardation (IUGR) were reviewed against cytomegalovirus and herpes simplex virus-1. Tests were repeated only for those with positive results. Recent infection of herpes simplex virus-1 and cytomegalovirus was evidenced by the presence of IgM in the female patients: incidence was 1.1% and 1.3% respectively. None of the neonates showed positive IgM for cytomegalovirus, but a single case showed a positive result for herpes simplex virus-1 IgM. Among the female patients, however, the presence of IgG indicated previous exposure to cytomegalovirus in 92% of cases and herpes simplex virus in 80.8%. It was concluded that although previous exposure to CMV and HSV-1 were found in high percentages in women experiencing infertility problems but did not appear to be associated with neonates exhibiting intrauterine growth retardation. Keywords: Abortion, CMV, HSV, Infertility problems, Intrauterine growth retardation